2011
DOI: 10.1126/scitranslmed.3002152
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Electroanatomic Mapping of Human Ventricular Arrhythmias with Electrocardiographic Imaging

Abstract: Sudden cardiac death due to ventricular tachycardia (VT) is a major health issue worldwide. Efforts to identify patients at risk, determine VT mechanisms, and effectively prevent and treat VT with a mechanism-based approach would benefit from continuous noninvasive imaging of the arrhythmia over the entire heart. This paper presents the first noninvasive images of human ventricular arrhythmias using electrocardiographic imaging (ECGI), highlighting the large diversity of human VT in terms of activation pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
159
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(167 citation statements)
references
References 47 publications
3
159
0
5
Order By: Relevance
“…7 In a clinical setting, Wang et al further validated this approach: in patients having ventricular tachycardia, the origin of activation was determined in an invasive electrophysiological procedure and compared with results from the epicardial potential inverse. 8 Consistent with findings from Taccardi et al, all 6 patients with epicardial origin showed a strictly negative reconstructed electrogram at the site of earliest activation, whereas an initial R wave was seen on the reconstructed epicardial electrogram for 7 out of 8 patients with endocardial or intramural sites of origin.…”
Section: Oosterhoff Et Alsupporting
confidence: 78%
See 1 more Smart Citation
“…7 In a clinical setting, Wang et al further validated this approach: in patients having ventricular tachycardia, the origin of activation was determined in an invasive electrophysiological procedure and compared with results from the epicardial potential inverse. 8 Consistent with findings from Taccardi et al, all 6 patients with epicardial origin showed a strictly negative reconstructed electrogram at the site of earliest activation, whereas an initial R wave was seen on the reconstructed epicardial electrogram for 7 out of 8 patients with endocardial or intramural sites of origin.…”
Section: Oosterhoff Et Alsupporting
confidence: 78%
“…Epicardial activation and repolarization times can be derived from these reconstructed electrograms, and under certain assumptions, some intramural excitation characteristics can be inferred before epicardial breakthrough. [6][7][8] This general approach was first suggested in the 1970s, and a variant of this method is used in the CardioInsight ECVUE system. [9][10][11][12][13] The inverse method used in the current study reconstructs the activation times on both the endocardial and epicardial surface, allowing discrimination of epicardial from endocardial foci.…”
mentioning
confidence: 99%
“…16 ECGI correctly identified the right or left ventricular location of the arrhythmia in 100 % of studies (n-23).…”
Section: Wang Et Al Studied 26 Ventricular Arrhythmias In 25 Patientsmentioning
confidence: 99%
“…44 Recently, ECGI has also been investigated as a potential additional imaging modality for mapping of VT. Wang et al demonstrated that ECGI accurately identifies the site of origin of VT in more than 90 % of cases when compared with invasive mapping. 45 Further, ECGI identified the mechanism of VT with a high degree of accuracy. Therefore, in addition to the expanding role in atrial arrhythmia, ECGI may emerge as an effective tool for mapping of VT.…”
Section: Advances In Imaging Techniques For Vt Ablationmentioning
confidence: 99%